Tetranychus bastosi Tuttle, Baker & Sales (Prostigmata: Tetranychidae) mites on Jatropha curcas (Linaeus) in Sergipe State, Brazil - Santos, Heloisa Oliveira dos; Silva-Mann, Renata; Boari, Alessandra de Jesus (Comunicata Scientiae, 2010)
Tetranychid mites represent important pests that attack different agricultural crops worldwide. In an evaluation of germplasm of physic nut, Jatropha curcas L. in the state of Sergipe, Brazil, the mites were observed on less vigorous plants with symptoms such as leaf blade reduction and curling. One hundred mites were collected from those plants and observed on microscope for taxonomic identification. The mites were assigned to the species Tetranychus bastosi (Acari: Tetranychidae). This is the first report of physic nut, J. curcas as host plant of T. bastosi in Brazil.